2020
DOI: 10.3390/biom10101375
|View full text |Cite
|
Sign up to set email alerts
|

A Diamine-PEGylated Oleanolic Acid Derivative Induced Efficient Apoptosis through a Death Receptor and Mitochondrial Apoptotic Pathway in HepG2 Human Hepatoma Cells

Abstract: Hepatocellular carcinoma (HCC) is the most common type of liver cancer. Our recent studies have shown that the diamine-(PEG)ylated oleanolic acid (OADP) has strong anti-tumor effects in HCCs. In this study, we evaluated the anti-tumor mechanisms of OADP in the HepG2 HCC cell line. The cytotoxicity results showed that HepG2 cell viability was markedly reduced, with a very low 50% of cell growth inhibitory concentration (IC50, 0.14 µg/mL). We then investigated the anti-tumor mechanisms of OADP in HepG2 cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Previous results have shown that OADP can induce apoptosis at very low concentrations in different cancer cell lines [ 16 , 17 ]. In the present study, we examine the potential of OADP as an anti-inflammatory agent and investigate the underlying molecular mechanism for this effect in LPS-stimulated RAW 264.7 macrophage cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous results have shown that OADP can induce apoptosis at very low concentrations in different cancer cell lines [ 16 , 17 ]. In the present study, we examine the potential of OADP as an anti-inflammatory agent and investigate the underlying molecular mechanism for this effect in LPS-stimulated RAW 264.7 macrophage cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our main objective in this article is to demonstrate the effectiveness of OADP as an anti-inflammatory agent and to study its behavior against inflammation induced by tumor promoters as TPA. OADP has been shown to be a very effective agent against tumor cell proliferation in HepG2 human hepatoma cancer cell line [ 17 ], and against inflammatory processes. Due to these results, we defend that OADP can be a good agent against tumorigenic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous chemical groups are being used in the synthesis of chemical derivatives of the most important triterpenoids in order to select derivatives that present a significant increase in efficiency in their bioactivity. Among them, acyl, aminoacyl, and dipeptidyl groups [ 26 , 27 , 41 , 42 ], pegylated and pegylated diamine derivatives [ 43 , 44 , 45 , 46 ], and even coumarin conjugates [ 47 ] stand out. In all cases, the anticancer, anti-inflammatory, antioxidant, or antiviral effects originally present in the molecules from which they are obtained are significantly increased.…”
mentioning
confidence: 99%
“…In this sense, different chemical groups are being used in the synthesis of these derivatives, significantly increasing their effectiveness [4]. Among these groups, acyls, aminoacyls and dipeptidyls [23,24,38,39], derivatives of pegylated and diamino-pegylated groups [40][41][42][43][44], and even derivatives with coumarin [45], with which their activities are significantly increased, stand out.…”
mentioning
confidence: 99%